Anti-Inflammatory Effects of Heparin and Its Derivatives: A Systematic Review - Sarah Mousavi; Mandana Moradi; Tina Khorshidahmad; Maryam Motamedi (Hindawi Limited, 2015)
Background. Heparin, used clinically as an anticoagulant, also has anti-inflammatory properties. The purpose of this systematic review was to provide a comprehensive review regarding the efficacy and safety of heparin and its derivatives as anti-inflammatory agents. Methods. We searched the following databases up to March 2012: Pub Med, Scopus, Web of Science, Ovid, Elsevier, and Google Scholar using combination of Mesh terms. Randomized Clinical Trials (RCTs) and trials with quasi-experimental design in clinical setting published in English were included. Quality assessments of RCTs were performed using Jadad score and Consolidated Standards of Reporting Trials (CONSORT) checklist. Results. A total of 280 relevant studies were reviewed and 57 studies met the inclusion criteria. Among them 48 studies were RCTs. About 65% of articles had score of 3 and higher according to Jadad score. Twelve studies had a quality score > 40% according to CONSORT items. Asthma (n=7), inflammatory bowel disease (n=5), cardiopulmonary bypass (n=8), and cataract surgery (n=6) were the most studied disease condition. Forty studies use unfractionated heparin (UFH) for intervention; the remaining studies use low molecular weight heparin (LMWH). Conclusion. Despite the conflicting results, heparin seems to be a safe and effective anti-inflammatory agent; although it is shown that heparin can decrease the level of inflammatory biomarkers and improves patient conditions, still more data from larger rigorously designed studies are needed to support use of heparin as an anti-inflammatory agent in clinical setting. However, because of the association between inflammation, atherogenesis, thrombogenesis, and cell proliferation, heparin and related compounds with pleiotropic effects may have greater therapeutic efficacy than compounds acting against a single target.